2016
DOI: 10.1017/jfm.2016.409
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of red blood cells in oscillating shear flow

Abstract: We present a three-dimensional computational study of fully deformable red blood cells of the biconcave resting shape subject to sinusoidally oscillating shear flow. A comprehensive analysis of the cell dynamics and deformation response is considered over a wide range of flow frequency, shear rate amplitude and viscosity ratio. We observe that the cell exhibits either a periodic motion or a chaotic motion. In the periodic motion, the cell reverses its orientation either by passing through the flow direction (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Decreased cell deformability and increased cell volume in T2DM have shown significant implications for microcirculatory alterations. Computational modeling and simulations help in predicting how RBCs behave in shear flow and providing insights into how viscous flow transforms RBC shapes, and vice versa, how deformed RBCs distort the surrounding flow (24,42,43,(78)(79)(80)(81)(82). Here, in order to address the effects of cell elasticity and shape on the biorheological behavior of individual T2DM RBCs, we investigate the dynamic behavior of T2DM RBCs in a microfluidic channel with constriction.…”
Section: Rheological Properties Of T2dm Rbcs In Shear Flowmentioning
confidence: 99%
“…Decreased cell deformability and increased cell volume in T2DM have shown significant implications for microcirculatory alterations. Computational modeling and simulations help in predicting how RBCs behave in shear flow and providing insights into how viscous flow transforms RBC shapes, and vice versa, how deformed RBCs distort the surrounding flow (24,42,43,(78)(79)(80)(81)(82). Here, in order to address the effects of cell elasticity and shape on the biorheological behavior of individual T2DM RBCs, we investigate the dynamic behavior of T2DM RBCs in a microfluidic channel with constriction.…”
Section: Rheological Properties Of T2dm Rbcs In Shear Flowmentioning
confidence: 99%
“…These previous studies can be categorized into the research field of biorheology because blood contains many red blood cells, which can be modelled as the capsules. In recent years, several researchers started to investigate the dynamics of capsules in unsteady flow (Zhao and Bagchi 2011;Matsunaga et al 2015;Zhu et al 2015;Cordasco and Bagchi 2016). In our previous study (Matsunaga et al 2015), we reported the capsule deformation under oscillating shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…However, in capillary and arterioles, it is reasonable to assume that the development of the branched structures is limited, and linear aggregates prevail. The average length of the RBC aggregates is dependent on shear forces and thus, varies periodically with changes in the blood flow [9, 10]. According to this relationship, the frequency of disassembling and reassembling the aggregates is controlled by the heartbeat, which evokes shear force modulation [11].…”
Section: Introductionmentioning
confidence: 99%
“…The aggregation and disaggregation of RBCs are dynamic processes. This shear-dependent variation is the primary cause of the non-Newtonian behavior of blood in human blood vessels [10]. As blood pressure increases to its peak, the flow velocity and shear rate gradually increase, and as the pressure decreases, the velocity and shear rate decrease.…”
Section: Introductionmentioning
confidence: 99%